Prevalence of bacterial vaginosis, trichomoniasis and vulvovaginal candidiasis in pregnant women attending Antenatal Clinic at the Kintampo Municipal Hospital, Kintampo - Gyasi Konadu, Dennis (2016)
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Science in Clinical Microbiology In the Department of Clinical Microbiology, School of Medical Science College of Health Science Kwame Nkrumah University Of Science And Technology, Kumasi,